Analysis of Intraoperative Frozen Pancreatic Resection Margin and Prediction of Postoperative Pancreatic Fistula Risk During Pancreatoduodenectomy - Brunner, Maximilian; Kovacevic, Jasna; Krautz, Christian; Merkel, Susanne; Hartmann, Arndt; Grützmann, Robert; Haller, Florian; Weber, Georg (Journal of the American College of Surgeons, 2022)
BACKGROUND: Pancreatic duct diameter and pancreatic texture are important predictive factors for a postoperative pancreatic fistula (POPF) and are assessed intraoperatively by the surgeon. However, surgical evaluation is arbitrary and difficult to objectify, especially in minimally invasive approaches in pancreatic surgery. STUDY DESIGN: We conducted a retrospective analysis of 275 patients that underwent pancreatoduodenectomy from 2012 to 2019 at our institution. Pancreatic duct diameter and pancreatic fibrosis were assessed by histopathologic examination of the pancreatic resection margin using intraoperative frozen sections and correlated with the occurrence of POPF and clinically relevant POPF (CR-POPF). RESULTS: The POPF and CR-POPF rates were 27% and 19%, respectively. Univariate analysis indicated that the indication for surgery, the surgically determined pancreatic duct diameter, and pancreatic texture, as well as the histopathologically determined pancreatic duct diameter and pancreatic fibrosis were significant predictive factors for POPF and CR-POPF. A multivariate analysis revealed histopathologically determined pancreatic duct diameter and pancreatic fibrosis as independent risk factors for POPF (OR [odds ratio] 2.3 [1.1 to 4.5], p = 0.022 and OR 2.4 [1.1 to 5.1], p = 0.023, respectively) and CR-POPF (OR 2.2 [1.1 to 4.8], p = 0.037 and OR 2.6 [1.1 to 6.1], p = 0.036). CONCLUSIONS: Histopathologically determined pancreatic duct diameter and pancreatic fibrosis are quantitatively measurable independent risk factors for POPF and CR-POPF. An intraoperative objective histopathologic evaluation of these parameters using frozen sections could support the surgical assessment of the pancreatic duct diameter and the pancreatic texture.
CRIS-Team Scopus Importer:2022-04-29